2002
DOI: 10.2460/javma.2002.221.811
|View full text |Cite
|
Sign up to set email alerts
|

Streptozocin for treatment of pancreatic islet cell tumors in dogs: 17 cases (1989–1999)

Abstract: Results suggest that streptozocin can be administered safely to dogs at a dosage of 500 mg/m2, IV, every 3 weeks when combined with a protocol for induction of diuresis and may be efficacious in the treatment of dogs with metastatic pancreatic islet cell tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 20 publications
4
32
0
2
Order By: Relevance
“…Unfortunately, medical management has minimal efficacy and the potential for severe side effects. Other drugs that have been evaluated include various chemotherapeutic agents such as streptozotocin and alloxan, which have direct effects on the pancreatic beta cells (Moore and others 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, medical management has minimal efficacy and the potential for severe side effects. Other drugs that have been evaluated include various chemotherapeutic agents such as streptozotocin and alloxan, which have direct effects on the pancreatic beta cells (Moore and others 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-eight treatments were administered to 17 dogs with an insulin-secreting tumor at variable times after surgery (Moore et al, 2002). Sixteen of 17 dogs had metastatic disease.…”
Section: Somatostatin Therapymentioning
confidence: 99%
“…However, a viable treatment protocol using streptozotocin in dogs has been described, and studies to determine its value in the treatment of insulin-secreting tumors have been reported (Moore et al, 2002;Northrup et al, 2013). The potential for serious adverse reactions has limited the use of these drugs for the treatment of insulinsecreting tumors in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, surgery alone is unlikely to be curative due to approximately 50% of dogs having metastatic disease, and most dogs develop progressive disease leading to recurrent hypoglycemia and secondary neuroglycopenia [1-3, 9, 10]. Therefore, medical treatments are warranted in attempt to inhibit progression of metastatic disease, ameliorate clinical signs, and extend survival times while maintaining quality of life [1][2][3][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%